Study on the Social Economic and Demographic Conditions of Slums in Rural Development: Implementing Sustainable Strategies for Slum Development in Rural Areas (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Urbanization develops we may expect that slums will in general become much quicker. Gulbarga is a second level city and a significant business center point for the Hyderabad-Karnataka district situated in the north eastern piece of Karnataka state. It draws in the rural people from adjoining areas and the city is going through quick changes as far as populace development just as in the level of urbanization because of which the ghetto populace is expanding. There are 60 slums that record for 11 of city's populace. This study plans to contribute some maintainable philosophies for better execution of ghetto development projects to propel the day to day environments of ghetto inhabitants. Ghetto cosmology has been worked to distinguish slums from exceptionally high-goal satellite information that will profit all partners. The created cosmology was approved with field study and the assistance of field photos, the physical and financial conditions were recorded. According to the ghetto cosmology, fundamental contributions for the Cellular Automata (CA) model were recognized and measures maps with scores were created. The reasonableness map was made by giving fitting load to the variables. At the point when the ghetto map arranged dependent on ghetto cosmology was overlaid on the end-product, the CA model yield has given solid outcomes with respect to current ghetto conveyance and furthermore a trace of the conceivable event of slums later on. Since the proposed land use plan for 2021 has been finished by the Urban Local Body (ULB), the reasonable region for creating moderate lodging stock was recommended for forestalling slums from emerging. The Spatial Decision Support System (SDSS) was worked for choosing ghetto development alternatives. The plan and running of the SDSS model were exhibited with one contextual analysis Borabai nagar ghetto to empower the ULB to apply the way to deal with other ghetto regions for successful execution of ghetto development programs.